1998
DOI: 10.1007/s004490050481
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide production: Experimental comparison of the performance of four mixing devices

Abstract: This investigation was undertaken with the objective to compare experimentally the performance of four different mixing devices for the production of the polysaccharide pullulan with Aureobasidium pullulans (2552). Fermentations were performed using identical bioreactors with respectively an assembly of three Rushton turbines (RTB), a helical ribbon impeller (HR) and two different reciprocating plates (RPB1, RPB2). Each mixing vessel had identical geometry and working volume (18 L). These four fermentations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…If the enzyme activity of cells changes, then the amount and content of the metabolism product also must change. This relationship is confirmed by the aforementioned and other studies [85][86][87][88], in which the main criterion of the evaluation of the results is the amount and quality of the synthesised product.…”
Section: Figsupporting
confidence: 85%
See 1 more Smart Citation
“…If the enzyme activity of cells changes, then the amount and content of the metabolism product also must change. This relationship is confirmed by the aforementioned and other studies [85][86][87][88], in which the main criterion of the evaluation of the results is the amount and quality of the synthesised product.…”
Section: Figsupporting
confidence: 85%
“…In some studies [71,86,88,96], the influence of stirring intensity on the molecular mass and physicochemical properties of the synthesised product has been established.…”
Section: Some Other Aspects Of Turbohypobiosismentioning
confidence: 99%
“…Experiments in our laboratory with Aspergillus niger [unpublished results] and Aureobasidium pullulans [22] already showed that the perforation diameter of the plates could have a profound impact on the product concentration and quality. Using a plate with larger perforations also decreases the level of shear stress to which the microorganisms are subjected.…”
Section: Comparative Fermentationmentioning
confidence: 99%
“…The high price of pullulan is attributed mainly to the difficulties in its production through fermentation such as high broth viscosity, low product yield, pigmentation, and product degradation [4]. Many factors can influence the pullulan production, including strain [5], temperature [6], pH [7], dissolved oxygen (DO) level (influenced by agitation, aeration) [8], substrate [9,10], trace element [11], fermentation model [12], mixing device [13], and so on. Lots of scientists and enterprisers in the world focus on it, but its synthetic mechanism of polysaccharide is still unknown, and there are different reports about its industrial fermentation.…”
Section: Introductionmentioning
confidence: 99%